2011
DOI: 10.1089/vim.2011.0024
|View full text |Cite
|
Sign up to set email alerts
|

Human-Leukocyte Antigen Class I Cw 1502 and Class II DR 0301 Genotypes Are Associated with Resistance to Severe Acute Respiratory Syndrome (SARS) Infection

Abstract: One-hundred and thirty confirmed cases of severe acute respiratory syndrome (SARS) were recruited to evaluate their anti-SARS-coronavirus (CoV) antibody status and human leukocyte antigen (HLA) types in September 2006, 3 y after the SARS outbreaks in Taiwan. Western blot assay showed that 6.9% of participants still had anti-spike and anti-nucleocapside antibodies. A case-control study of the association of HLA with SARS revealed that the HLA-Cw1502 and DR0301 alleles conferred resistance against SARS infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
111
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(114 citation statements)
references
References 28 publications
1
111
0
2
Order By: Relevance
“…The antigen presentation of SARS-CoV mainly depends on MHC I molecules [24], but MHC II also contributes to its presentation. Previous research shows numerous HLA polymorphisms correlate to the susceptibility of SARS-CoV, such as HLA-B*4601, HLA-B*0703, HLA-DR B1*1202 [25] and HLA-Cw*0801 [26], whereas the HLA-DR0301, HLA-Cw1502 and HLA-A*0201 alleles are related to the protection from SARS infection [27]. In MERS-CoV infection, MHC II molecules, such as HLA-DRB1*11:01 and HLA-DQB1*02:0, are associated with the susceptibility to MERS-CoV infection [28].…”
Section: Antigen Presentation In Coronavirus Infectionmentioning
confidence: 99%
“…The antigen presentation of SARS-CoV mainly depends on MHC I molecules [24], but MHC II also contributes to its presentation. Previous research shows numerous HLA polymorphisms correlate to the susceptibility of SARS-CoV, such as HLA-B*4601, HLA-B*0703, HLA-DR B1*1202 [25] and HLA-Cw*0801 [26], whereas the HLA-DR0301, HLA-Cw1502 and HLA-A*0201 alleles are related to the protection from SARS infection [27]. In MERS-CoV infection, MHC II molecules, such as HLA-DRB1*11:01 and HLA-DQB1*02:0, are associated with the susceptibility to MERS-CoV infection [28].…”
Section: Antigen Presentation In Coronavirus Infectionmentioning
confidence: 99%
“…Several studies suggest that antibodies against non-SARS-CoVs are highly prevalent in the general population including in children, suggesting that most individuals have been infected by CoVs and have potentially developed a certain degree of (protective) immune response [43,44]. There is no clear evidence on whether and how prior exposure to a strain of CoV can produce permanent immunity against the strain species or even cross-immunity for other CoV species [43].…”
Section: Pathogenesis Disease Severity and Epidemic Spreadmentioning
confidence: 99%
“…Right on the year of the outbreak, a study with a few dozens of SARS patients indicated an association of the HLA-B*46: 01 allele with the severity of the infection in Taiwanese population [14] . Later, a casecontrol study in the same population revealed that the HLA-C*15: 02 and -DRB1*03: 01 alleles confer resistance against SARS infection [98] . Nevertheless, a cohort of 95 SARS-recovered patients from Guangdong, southern China, miss to show any association between the development of the disease and their HLA profile [99] , despite a study with 90 Chinese patients from Hong Kong confirmed the HLA-DRB1*03: 01 as a protective allele and unveiled another risk allele, the HLA-B*07: 03, despite not confirming the B*46: 01 [100] .…”
Section: Severe Acute Respiratory Syndrome (Sars)mentioning
confidence: 99%